2023
DOI: 10.1111/fwb.14156
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming and drying act independently on developmental responses for two amphibian species

Elizabeth J. Shadle,
William A. Hopkins,
Lisa K. Belden
et al.

Abstract: Climate change is affecting freshwater habitats worldwide through multiple, interacting pressures that influence the survival, distribution, and persistence of freshwater organisms. Temporary freshwater habitats, or those that dry seasonally, can exhibit wide‐ranging variability in temperature and drying regimes. Aquatic organisms with complex life cycles (e.g., aquatic and terrestrial life stages) often rely on temporary freshwaters to complete their life cycles and have specific adaptations to cope with thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In fact, Shadle and al. (2023) compared experimentally climate change effects on habitat specialist wood frogs (Lithobates sylvaticus) and more generalist spring peepers (Pseudacris crucifer)(Shadle et al, 2023). They demonstrated that warming accelerates the duration to metamorphosis, while drying leads to diminished body size at metamorphosis in both species.…”
mentioning
confidence: 99%
“…In fact, Shadle and al. (2023) compared experimentally climate change effects on habitat specialist wood frogs (Lithobates sylvaticus) and more generalist spring peepers (Pseudacris crucifer)(Shadle et al, 2023). They demonstrated that warming accelerates the duration to metamorphosis, while drying leads to diminished body size at metamorphosis in both species.…”
mentioning
confidence: 99%